Identification of Periopathogens in Atheromatous Plaques Obtained from Carotid and Coronary Arteries. (17th June 2021) - Pavlic, Verica; Peric, Dejan; Kalezic, Ivana Stosovic; Madi, Marwa; Bhat, Subraya G.; Brkic, Zlata; Staletovic, Danijela
Abstract : Increasing attention has been paid to the possible link between periodontal disease and atherosclerosis over the past decade. The aim of this study is to investigate the presence of five periopathogens: Porphyromonas gingivalis ( P.g. ), Aggregatibacter actinomycetemcomitans ( A.a. ), Tannerella forsythia ( T.f. ), Treponema denticola ( T.d. ), and Prevotella intermedia ( P.i. ) in atheromatous plaques obtained from the carotid and coronary arteries in patients who underwent coronary artery bypass graft surgery and carotid endarterectomy. Group I (carotid arteries) consisted of 30 patients (mean age: 54.5 ± 14.8 ), and group II (coronary arteries) consisted of 28 patients (mean age: 63 ± 12.1 ). Clinical periodontal examinations consisted of plaque index, gingival index, sulcus bleeding index, and periodontal probing depth and were performed on the day of vascular surgery. The presence of periopathogens in periodontal pockets and atherosclerotic vessels was detected using polymerase chain reaction. In both subgingival plaque and atherosclerotic plaque of carotid arteries, P.g., A.a., T.f., T.d., and P.i. were detected in 26.7%, 6.7%, 66.7%, 10.0%, and 20.0%, respectively, while for coronary arteries, P.g . was detected in 39.3%, A.a . in 25%, T.f . in 46.4%, T.d. in 7.1%, and P.i. in 35.7%. The presence of five periopathogens in carotid and coronary atherosclerotic vessels showed correlation in regard to the degree of periodontal inflammation. The present study suggests the relationship between periodontal pathogenic bacteria and atherogenesis. Further studies are necessary in relation to the prevention or treatment of periodontal disease that would result in reduced mortality and morbidity associated with atherosclerosis.